Parametric Study for Structural Reinforcement Methods of Disposal Container for NPP Decommissioning Radioactive Waste - Kang, Hyungoo; Dho, Hoseog; Lim, Jongmin; Cho, Yeseul; Cho, Chunhyung (Journal of nuclear fuel cycle and waste technology (Online), 2023)
This paper described a method for analyzing the structural performance of a metal container used for disposing radioactive waste generated during the decommissioning of a nuclear power plant, and numerical analysis results of a method for reinforcing the container. The containers to be analyzed were those that can be used in near-surface and landfill disposal facilities scheduled to be operated at the Gyeongju radioactive waste disposal facility. Structural reinforcement of the container was performed by lattice reinforcement, column reinforcement, and bottom plate reinforcement. Accordingly, a total of 14 reinforcement cases were modeled. The external force causing damage to the container was set equivalent to the impact of a 9-m fall, accounting for the height of the vault at the near-surface disposal facility. The reinforcement methods with a high contribution to the structural performance of the container were concluded to be lattice and column reinforcements.